Why are sex and gender important to basic physiology and translational and individualized medicine? - Miller, Virginia M. (American Physiological Society, 2014)
Sex refers to biological differences between men and women. Although sex is a fundamental aspect of human physiology that splits the population in two approximately equal halves, this essential biological variable is rarely considered in the design of basic physiological studies, in translating findings from basic science to clinical research, or in developing personalized medical strategies. Contrary to sex, gender refers to social and cultural factors related to being a man or a woman in a particular historical and cultural context. Unfortunately, gender is often used incorrectly by scientists and clinical investigators as synonymous with sex. This article clarifies the definition of sex and gender and reviews evidence showing how sex and gender interact with each other to influence etiology, presentation of disease, and treatment outcomes. In addition, strategies to improve the inclusion of female and male human beings in preclinical and clinical studies will be presented, and the importance of embedding concepts of sex and gender into postgraduate and medical curricula will be discussed. Also, provided is a list of resources for educators. In the history of medical concepts, physiologists have provided pivotal contributions to understanding health and disease processes. In the future, physiologists should provide the evidence for advancing personalized medicine and for reducing sex and gender disparities in health care.